Investigating the impact of spike protein mutations on SARS-CoV-2 virulence in benin using network centrality and molecular docking approaches - Thai, Quan Ke; Huynh, Phuoc; Nguyen Thi Thuong, Huyen; Quan, Quoc-Dang (Vietnam Journal of Biotechnology, 2023)
The COVID-19 pandemic is ongoing and spreading around the world, which means a continuous increase in the number of infections and death. SARS-CoV-2 constantly rapidly stored mutation in the Spike gene to adapt with the host cell. The Spike gene encoded spike protein directly interacts with hACE2 on the human cell surface. Herein, using the network centrality and molecular docking approaches, we detected key mutations that positively affect spike protein. Based on network centrality, we demonstrate that the A23403G (D614G) mutation in the Spike gene is the center of a network which means this mutation has a positive effect on the virus. In addition, analyzing the interaction of spike protein with hACE2, we highlighted that the mutation appeared in the RBD region by changing the electrostatic energy of the complex. Remarkably, mutations N440K, L452R, T478K, E484K, Q493R, and Q498R increased binding free energy of Spike-hACE2 complex due to the change of the side chain into a positive charge. The Eta, Delta, and Omicron variants existed in one or more of these mutations resulting in higher binding free energy and binding affinity than the Wuhan variant indicating sounder interaction with hACE2. In general, mutations appearing on the spike protein tended to cause the surface to become positively charged in order to interact easily with the negative surface of the hACE2 receptor.